Tendo a cruz por bandeira: movimentos religiosos contra-hegemônicos na América Latina inspirando as histórias da formação e a prática de agentes religiosos em movimentos populares no Rio Grande do Sul (1970-1980) - Bonotto, Cléo Adriano Sabadi (2008)
This dissertation aims to comprehend the process of formation and acting of religious preachers who got engaged in social movement in the end of 1970 decade and the beginning of the 1980, in Rio Grande do Sul RS/BRAZIL. In spite of Brazil was within a dictatorial regime, and in this period there were no workers trade neither politics parties that were allowed to act or to express the folk classes interest; because of it other civil organization had to play this role, some of them were ready to organization had to play this role. However, the progressive sectors to be allowed to be active in the Catholic Church this institution was supposed to change, and see the real world; because only in this way the Church could be sensitive about the social problems. Nevertheless, a religion needs to keep a continuity meaning, even in changing times, in this way, the dissertation discuss the transformations occurred with the Catholic Church in the 20th Century, mainly with the liberation theology. The Centro de Orientação Missionária s role was analyzed referring to the theoretical formation of leaders and the organization of social movement. Trying to comprehend the formation s role in poor communities, staring to the pioneers Franciscans in Lomba do Pinheiro, it is located in the suburbs of Porto Alegre; also the participation of religious people in the landless workers movement MST ( Movimento dos Trabalhadores Sem Terra) organization in Rio Grande do Sul was analyzed as a practical period of formation to these religious preachers that are going to influence their participation in the social movement, presupposing that these three cases complete themselves, theoretical formation, inserted and practice. In order to develop this search, interviews with religious people, pastoral people and other preachers that were involved directly with this Movimentos were used.